2017
DOI: 10.1109/comst.2016.2594120
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Green Tradeoffs: Progresses, Challenges, and Impacts on 5G Networks

Abstract: With years of tremendous traffic and energy consumption growth, green radio has been valued not only for theoretical research interests but also for the operational expenditure reduction and the sustainable development of wireless communications. Fundamental green tradeoffs, served as an important framework for analysis, include four basic relationships: spectrum efficiency (SE) versus energy efficiency (EE), deployment efficiency (DE) versus energy efficiency (EE), delay (DL) versus power (PW), and bandwidth … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
176
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(178 citation statements)
references
References 210 publications
(286 reference statements)
2
176
0
Order By: Relevance
“…Another survey article [52] provided a comprehensive review of existing radio interference and resource management schemes for 5G radio access networks and classified the existing schemes in terms of radio interference, energy efficiency and spectrum efficiency. In the direction of energy-efficient 5G communications, authors in [53,54] provided a detailed survey of the existing works in the areas of energy-efficient techniques for 5G networks and analyzed various green trade-offs, namely, spectrum efficiency versus energy efficiency, delay versus power, deployment efficiency versus energy efficiency, and bandwidth versus power for the effective design of energy-efficient 5G networks [53]. In addition, several survey and overview papers exist in the area of 5G enabling technologies such as massive MIMO [7,[55][56][57], mmWave [7,8,58], Non Orthogonal Multiple Access (NOMA) [59,60], cellular and heterogeneous networks [61][62][63], Internet of Things (IoT) [66,68], Machine to Machine (M2M) communication [64][65][66] and Device to Device (D2D) communication [67].…”
Section: B Related Workmentioning
confidence: 99%
“…Another survey article [52] provided a comprehensive review of existing radio interference and resource management schemes for 5G radio access networks and classified the existing schemes in terms of radio interference, energy efficiency and spectrum efficiency. In the direction of energy-efficient 5G communications, authors in [53,54] provided a detailed survey of the existing works in the areas of energy-efficient techniques for 5G networks and analyzed various green trade-offs, namely, spectrum efficiency versus energy efficiency, delay versus power, deployment efficiency versus energy efficiency, and bandwidth versus power for the effective design of energy-efficient 5G networks [53]. In addition, several survey and overview papers exist in the area of 5G enabling technologies such as massive MIMO [7,[55][56][57], mmWave [7,8,58], Non Orthogonal Multiple Access (NOMA) [59,60], cellular and heterogeneous networks [61][62][63], Internet of Things (IoT) [66,68], Machine to Machine (M2M) communication [64][65][66] and Device to Device (D2D) communication [67].…”
Section: B Related Workmentioning
confidence: 99%
“…First, the constant circuit power p c m is considered during a time slot 39 and the energy consumption is given by p c m T. Second, the amount of consumed energy for conducting sensing operations can be obtained by E i m = N m , where > 0 is the constant coefficient and N m is the amount of data to be transmitted. First, the constant circuit power p c m is considered during a time slot 39 and the energy consumption is given by p c m T. Second, the amount of consumed energy for conducting sensing operations can be obtained by E i m = N m , where > 0 is the constant coefficient and N m is the amount of data to be transmitted.…”
Section: Energy Consumption Modelmentioning
confidence: 99%
“…For instance, IoT can serve massive access nodes for wireless service in the scenario of the ultradense networks (UDN) in 5G [1][2][3][4]. It is shown that there are as many as over three thousands of papers in IEEE exploring over the study of IoT, where the number of the journal papers is over six hundreds.…”
Section: Introductionmentioning
confidence: 99%